PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TER-HADAP KOMITMEN ORGANISASI (STUDI KASUS PADA HOTEL â€œBINTANG LIMAâ€ PEKANBARU) - Hasibuan, Rahmi Sarah; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research aims to recognize the organizational culture?s influence and the job satisfaction of the organization?s commitment partial and simultaneous. This study uses questionnaires to distribute to 26 responders to Hotel Bintang Lima employees. Next data were prepared using descriptive analysis and statistical analysis using SPSS 23, validating tests, reability, linear regression tests simple, linear regression tests multiple, determinative analysis (R2) and hypothetical tests with t (partial) and simultaneous F (simultaneous) tests. Research results show that testing the first hypothesis is the organization?s culture?s test of the organization?s commitment is t countdown (4,687) > t tabel (2,062), meaning the organization?s culture has a significant impact on the organization?s commitment. Second, job satisfaction is t count (4,528) > t table (2,062) meaning that job satisfaction has a significant impact on the organization?s commitment. The test F count (29,922) > F table (3,42) means organizational culture and job satisfaction simultaneously make a significant impact on the organization?s commitment.